An Overview of the Biological Effects of Some Mediterranean Essential Oils on Human Health. (5th November 2017) - Elshafie, Hazem S.; Camele, Ippolito
Abstract : Essential oils (EOs), extracted from aromatic plants, are interesting natural products and represent an important part of the traditional pharmacopeia. The use of some EOs as alternative antimicrobial and pharmaceutical agents has attracted considerable interest recently. Most of the EOs and their single constituents have been reported to inhibit several phytopathogens, human pathogens, and insects as well as their effective uses in food and pharmaceutical industries. The current review discussed the chemical composition and bioactivity of some important EOs extracted from some Mediterranean plants and their principal bioactive single constituents. Information has been furnished on the mechanisms, mode of actions, and factors affecting the bioactivity of some single constituents from different Mediterranean plant EOs. The current review gives an insight into some common plant EOs belonging to Lamiaceae, Apiaceae, Rutaceae, and Verbenaceae families commonly growing in Mediterranean region. Further information has been provided about the medical uses of some EOs for several human diseases covering the pharmacological effects (anti-inflammatory, antioxidant, and anticarcinogenic). The antimicrobial effects have been also considered in the current review. Although plant EOs are considered promising natural alternatives for many chemical drugs, they still need more specific research for wide application especially in food and pharmaceutical industries.